Anti-collapse performance of concrete-filled steel tubular composite frame with assembled tensile steel brace under middle column removal. (1st September 2022) - Wang, Jing-Xuan; Shen, Ya-Jun; Gao, Shan; Wang, Wen-Da
Highlights: Two CFST composite frames were tested under column removal. Assembled tensile steel braces delayed the failure of upper beam and improved the performance of frame. Splint bolt connection configuration can effectively improve the bearing capacity of the frame. The collapse resistance of the structure is calculated by considering the effect of the steel braces. Abstract: To study the effect of assembled tensile steel brace on the progressive collapse resistance of concrete-filled steel tubular (CFST) structures, two 1/4-scaled two-bay two-story composite frames with CFST columns and profiled steel–concrete composite beams were tested pseudo-statically under a middle column removal scenario. The vertical load–displacement responses and failure modes of two specimens were analyzed. Especially, the effects of assembled tensile steel braces on the anti-collapse performance of the frames were discussed. Experimental results show that the assembled tensile steel braces delayed the failure of the upper beam and significantly improved the structural bearing capacity and ductility of the frame. The horizontal reaction forces of the specimens are compressive forces due to the compressive arch action in the initial loading stage, and they change from compression to tension due to the catenary action. Numerical parametric analysis indicates that the splint bolt connection configuration can effectively improve the bearing capacity of the frame models by increasing the bolt preload and friction coefficient. Furthermore, the collapse resistance of the structure is calculated based on the simplified elastic theory method, considering the effect of the steel braces. It is believed that the assembled tensile brace between CFST columns could be used as a reinforcement method to improve the collapse resistance of the framed structure.